Optimizing an International Network of Partially Owned Plants Under Conditions of Trade Liberalization - Dasu, Sriram; de la Torre, José (Management Science, 1997)
For the last four decades the preferred economic philosophy in much of Latin America was that of import-substituting industrialization. As a result multinational corporations (MNCs) approached different countries with the expectation that each plant would primarily serve its domestic market. Each of these plants was partially owned by the MNC. Beginning in the late 1980s, Latin America countries began decreasing barriers to cross-border trade. This made competition between the units belonging to a common network possible for the first time. Operations which had subsisted side by side in spite of differences in costs and quality of output, and which were under the control of different owners now found themselves in competition with one another and having to rationalize their efforts. In this paper we analyze the problem of operating a network of plants under conditions of free trade and exchange rate fluctuations, when the firms that compose it are partially-owned subsidiaries of an MNC. A model of three subsidiaries and four countries is developed for one industry, based on actual corporate and economic data. We study the problem of coordinating the activities of the subsidiaries and allocating the gains arising from coordination.